2003
DOI: 10.1161/01.res.0000091828.36599.34
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Attenuates Glucose-Mediated Cell Growth Arrest and Apoptosis in Human Microvessel Endothelial Cells

Abstract: Abstract-Heme oxygenase-1 (HO-1) is a stress protein that has been suggested to participate in defense mechanisms against agents that may induce oxidative injury, such as heme and inflammatory molecules. Incubation of endothelial cells in a high-glucose (33 mmol/L) medium for 7 days resulted in a decrease of HO activity by 34% and a decrease in HO-1 and HO-2 proteins compared with cells exposed to low glucose (5 mmol/L) (PϽ0.05) or cells exposed to mannitol (33 mmol/L). Overexpression of HO-1 was coupled with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(148 citation statements)
references
References 54 publications
4
143
0
Order By: Relevance
“…42 HO-1 attenuates glucose-mediated cell growth arrest and apoptosis in human micro-vessel endothelial cells. 43 These may explain why mice pretreated with RvD1 showed higher expression of HO-1 and TJ proteins and decrease of apoptosis cells in TUNEL compared with the LPS group in this study. Moreover, pro-injected with Znpp mice showed more positive cells in TUNEL section compared with LPS þ RvD1 group, but the apoptosis cells in the LPS group proved no marked difference with the LPS þ Znpp group.…”
Section: Rvd1 Reduces Deterioration Of Tj Proteins W Xie Et Almentioning
confidence: 70%
“…42 HO-1 attenuates glucose-mediated cell growth arrest and apoptosis in human micro-vessel endothelial cells. 43 These may explain why mice pretreated with RvD1 showed higher expression of HO-1 and TJ proteins and decrease of apoptosis cells in TUNEL compared with the LPS group in this study. Moreover, pro-injected with Znpp mice showed more positive cells in TUNEL section compared with LPS þ RvD1 group, but the apoptosis cells in the LPS group proved no marked difference with the LPS þ Znpp group.…”
Section: Rvd1 Reduces Deterioration Of Tj Proteins W Xie Et Almentioning
confidence: 70%
“…Angiotensin II has been shown to increase endothelial cell death, an effect that is reversed by increased haem oxygenase-1 gene expression [20,31]. Inhibition of haem oxygenase activity has been shown to exacerbate both the inflammatory response in the arterial wall and to enhance endothelial cell death and the expression of adhesion molecules in animal models of atherosclerosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that human microvascular endothelial cells, when exposed to high glucose concentrations, manifest an increase in apoptosis [20]. We therefore hypothesised that hyperglycaemia-mediated oxidative stress results in endothelial cell injury and that this may be reflected by a concurrent increase in CECs.…”
Section: Introductionmentioning
confidence: 97%
“…Plasma creatinine levels were measured using a commercial kit (Aldrich/Sigma), according to the manufacturer's recommendation. In renal tissue, superoxide measurements were performed using a cytochrome C assay that has been described previously (31).…”
Section: Animal Treatmentmentioning
confidence: 99%
“…Western Blot Analysis of HO-1 and HO-2. Homogenates were used as a source for the measurement of HO-1 and HO-2 proteins as described previously (31). Tissues were lysed in a buffer (lysis buffer B) that consisted of 0.5% Nonidet P-40, 0.5% deoxycholate, and 10 mM EDTA in Tris-buffered saline (20 mM Tris and 150 mM NaCl [pH 7.4]) that contained 10 g/ml each of leupeptin, antipain, and pepstatin and 1 mM PMSF.…”
mentioning
confidence: 99%